Regulation of Energy Metabolism by Receptor Tyrosine Kinase Ligands - Zhao, Meng; Jung, Yunshin; Jiang, Zewen; Svensson, Katrin J. (Frontiers in Physiology, 2020)
Metabolic diseases, such as diabetes, obesity, and fatty liver disease, have now reached epidemic proportions. Receptor tyrosine kinases (RTKs) are a family of cell surface receptors responding to growth factors, hormones, and cytokines to mediate a diverse set of fundamental cellular and metabolic signaling pathways. These ligands signal by endocrine, paracrine, or autocrine means in peripheral organs and in the central nervous system to control cellular and tissue-specific metabolic processes. Interestingly, the expression of many RTKs and their ligands are controlled by changes in metabolic demand, for example, during starvation, feeding, or obesity. In addition, studies of RTKs and their ligands in regulating energy homeostasis have revealed unexpected diversity in the mechanisms of action and their specific metabolic functions. Our current understanding of the molecular, biochemical and genetic control of energy homeostasis by the endocrine RTK ligands insulin, FGF21 and FGF19 are now relatively well understood. In addition to these classical endocrine signals, non-endocrine ligands can govern local energy regulation, and the intriguing crosstalk between the RTK family and the TGF receptor family demonstrates a signaling network that diversifies metabolic process between tissues. Thus, there is a need to increase our molecular and mechanistic understanding of signal diversification of RTK actions in metabolic disease. Here we review the known and emerging molecular mechanisms of RTK signaling that regulate systemic glucose and lipid metabolism, as well as highlighting unexpected roles of non-classical RTK ligands that crosstalk with other receptor pathways.